Investigations of temperature and power effects on Cu(In, Ga)Se2 thin‐film formation during a 3‐stage hybrid co‐sputtering/evaporation process. (5th September 2017) - Posada, Jorge; Jubault, Marie; Bousquet, Angélique; Tomasella, Eric; Lincot, Daniel
Abstract: This work explores a strategy to bring together the advantages of co‐evaporation and sputtering by developing a hybrid co‐sputtering/evaporation process, where copper, indium, and gallium are sputtered with the thermal evaporation of selenium. A 3‐stage hybrid co‐sputtering/evaporation process for Cu(In, Ga)Se2 (CIGS) thin films solar cells has been developed by controlling the deposition parameters (temperature, sputtering power, and evaporation). (In, Ga)2 Se3 layers are deposited in the first stage, followed by Cu2 − x Se and Cu2 − x Se/(In, Ga)2 Se3 layers. Material properties at different steps were studied in detail by X‐ray fluorescence, energy dispersive X‐ray, scanning electron microscopy, glow discharge optical emission spectroscopy, Raman spectroscopy, and X‐ray diffraction. Solar cells were completed leading to 9.7% efficiency. Abstract : A 3‐stage hybrid cosputtering/evaporation sequence for Cu(In, Ga)Se2 (CIGS) absorbers has been developed by controlling the deposition parameters (temperature, sputtering power, and evaporation). Each step of this sequence has been optimized. (In, Ga)2 Se3 layers are deposited in the first stage, followed by Cu2‐x Se and Cu2‐x Se/(In, Ga)2 Se3 layers. Solar cells were completed leading to 9.7% efficiency. These first results open a new avenue for combining the advantages of coevaporation in terms of controlling composition gradients within CIGS films and those of sputtering for large‐scale industrial applications.